2020
DOI: 10.1021/acsami.0c08220
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Cobalt Selenide/Graphene Counter Electrode for Efficient Dye-Sensitized Solar Cells with Co2+/3+-Based Redox Couple

Abstract: In this study, we demonstrate a facile, one-pot, and low-temperature (∼85 °C) chemical bath method for the preparation of a composite of cobalt selenide/graphene (Co 0.85 Se/Gr) as the electrocatalyst for the counter electrode (CE) of dye-sensitized solar cells (DSSCs) with a cobalt-based electrolyte. The Co 0.85 Se/Gr composite film was envisaged to have the advantages of both components, that is, the high electrochemical surface area of Co 0.85 Se and the straight paths for electron transfer from Gr. The DSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 63 publications
2
25
0
Order By: Relevance
“…Platinum (Pt) is widely used as a conventional CE material in DSSCs due to its superior catalytic activity toward the redox reaction of conventional I − /I 3 − electrolyte and high electrical conductivity (9.43 × 10 6 S/m) [ 9 ]. However, the high cost of Pt (4.6 USD/m 2 for a 5 nm-thick Pt film) hinders its large-scale application in DSSCs [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platinum (Pt) is widely used as a conventional CE material in DSSCs due to its superior catalytic activity toward the redox reaction of conventional I − /I 3 − electrolyte and high electrical conductivity (9.43 × 10 6 S/m) [ 9 ]. However, the high cost of Pt (4.6 USD/m 2 for a 5 nm-thick Pt film) hinders its large-scale application in DSSCs [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the replacement of Pt-CE, numerous studies have demonstrated, using, for example, carbonaceous materials (e.g., graphene, carbon nanotubes, active carbon, graphite, carbon black) [ 12 ], conducting polymers (CPs) (e.g., polyaniline, polypyrrole, and poly(3,4-ethylene dioxythiophene) (PEDOT: PSS)) [ 13 ], transition metal compounds (e.g., carbides, nitrides, oxides) [ 14 ], and various hybrids or composites materials [ 15 ], which are about 10 to 10,000 times cheaper than that of Pt-CE [ 10 ]. Among them, nanostructures of metallic Ni and its compounds (e.g., oxides, sulfides, ternary sulfides, phosphides) are potentially suitable CE materials because of their decent corrosion resistance to the I − /I 3 − redox mediator and low cost [ 11 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the rich distribution and size of nanopores can be regulated and controlled by pyrolysis temperature and activation, thereby forming more nanopores to expose more active areas and promote the ability of electron transfer [35,36], but the appropriate temperature and proportion are more conducive to the recombination of AC and CoPc, as well as providing more adhesion sites for CoPc. The XRD patterns of AC/CoPc series composite catalysts (Figure 3a) all correspond to Co (JCPDS 15-0806) [37] and graphite (JCPDS 01-0646) [38]. AC/CoPc-800-1-2 and AC/CoPc-900-1-2 exhibit that the broadened peak at 25.7 • is ascribed to the (002) plane of graphite (JCPDS 01-0646), but AC/CoPc-800-1-2 has a larger broad peak at 25.7 • , which manifests that the carbonization temperature of 800 °C is more conducive to the formation of carbon with small graphite domains [39].…”
Section: Resultsmentioning
confidence: 99%
“…Polymers modified by thin films of binary d-metal chalcogenides belong to the composite materials as well. These composites promise to be valuable in solar energy conversion [1,2], thermoelectrics [3,4], photocatalysis [5], photodetectors [6], light-emitting diodes [7] and so on. Group III metal (Ga, In and Tl) composite materials binary or ternary compounds combined with group VI nonmetals (S, Se and Te) have very important and unique physical properties to technology and modern science.…”
Section: Introductionmentioning
confidence: 99%